Failure of Thrombolytic Therapy in Patients with Myocardial Infarction Is Associated with High Plasma Levels of Factor VII Antigen - Holm, Johan; Tödt, Tim; Berntorp, Erik; Erhardt, Leif (Thrombosis and Haemostasis, 1998)
Thrombolytic therapy in acute myocardial infarction fails to re-establish coronary blood flow in a significant number of patients. One reason for this may be haemostatic imbalance. We investigated whether coagulation factor VII antigen (FVIIag), fibrinogen and protein C were related to reperfusion. Plasma from 45 patients was drawn before treatment and reperfusion assessed by means of continuous, on-line, vector-ECG analysis.Amongthe 17 patients with no reperfusion, FVIIag levels were significantly higher than among the 28 with signs of reperfusion (560 vs. 410 μg/l median, p = 0.006). Protein C levels where higher in the group with successful reperfusion (1.10 vs. 1.01 U/ml median, p = 0.03), whereas no difference was seen in fibrinogen levels. The findings were not influenced by plasma-triglycerides, body-mass index, age or time between onset of chest pain and thrombolytic therapy.The results suggest that FVII is of importance for the formation as well as resolution of coronary clots.